Numerical study of laminar flow and heat transfer in square channel with 30° inline angled baffle turbulators - Promvonge, Pongjet; Jedsadaratanachai, Withada; Kwankaomeng, Sutapat (My University, 2010)
The article presents a numerical investigation on periodic laminar flow and heat transfer behaviors in a three-dimensional isothermal wall square-channel fitted with 30°-angled baffles on two opposite channel walls. The computations based on the finite volume method with the SIMPLE algorithm have been conducted for the fluid flow in terms of Reynolds numbers ranging from 100 to 2000. To generate a pair of streamwise counter-rotating vortex (P-vortex) flows through the tested channel, the angled baffles with the attack angle of 30° are mounted periodically and inline arrangement on the lower and upper channel walls. Effects of different baffle heights and three pitch ratios on heat transfer and flow behaviors in the channel are examined. It appears that P-vortex flows help to induce impinging flows over the baffle leading end side and the inter-baffle cavity walls resulting in drastic increase in heat transfer rate over the test channel. The computational results reveal that the maximum thermal enhancement factors for the baffle with PR = 1, 1.5 and 2 are found to be about 3.6, 3.8 and 4.0 at BR = 0.2, 0.2 and 0.15, respectively. © 2010 Elsevier Ltd. All rights reserved.
Keywords: Angled baffle; Heat transfer; Laminar flow; Periodic flow; Square channel; Turbulator